Shape-controlled synthesis of MnO2 nanostructures with enhanced electrocatalytic activity for oxygen reduction - Xiao, Wei (2012)
In this work, three types of MnO2 nanostructures, viz., microsphere/nanosheet core−corona hierarchical architectures, one-dimensional (1D) nanorods, and nanotubes, have been synthesized employing a simple hydrothermal process. The formation mechanisms have been rationalized. The materials have been thoroughly characterized by X-ray diffraction, Brunauer−Emmett−Teller spectrometry, field-emission scanning electron miscroscopy, energy dispersive spectroscopy, and transmission electron microscopy. The microsphere/nanosheet core−corona hierarchical structures are found to be the layered birnessite-type MnO2, while 1D nanorods and nanotubes are of the α-MnO2 phase. These MnO2 nanostructures are used as a model system for studying the shape/phase-dependent electrocatalytic properties for the oxygen reduction reaction, which have be investigated by cyclic and linear sweep voltammetry. It is found that α-MnO2 nanorods/tubes possess largely enhanced electrocatalytic activity compared to birnessite-type MnO2 core−corona spheres despite the latter having a much higher specific surface area. The vast difference in electrocatalytic activity is discussed in terms of crystal structure, oxygen adsorption mode, and exposed crystal facets.